The Antecedents of Organizational Citizenship Behavior in the Public Sector: A study in the Effect of Organizational Justice Determinants with the Mediating Role of Job Satisfaction(Applied to the Egyptian Ministry of Transportation) - Fahim, Marwa (The Arab Journal of Administration, 2023)
Organizational citizenship behavior (OCB) is one of the most remarkable topics and promising constructs that have lately emerged in the modern management thought. OCB is generally influenced by individuals’ perceptions, behaviors, and attitudes towards the organization and the work. In this context, many antecedents of OCBs might be involved. Two of the most important antecedents are introduced here which are; organizational justice (OJ) and job satisfaction (JS). Therefore, the purpose of this research paper is to gain insight into the way in which OJ perceptions of public officials can affect their OCBs. In other words, it aims at explaining the link between OJ and OCB considering JS as a mediating variable. Indeed, the study applied the quantitative analysis method with an explanatory research design typology. For theoretical intents, it adopted the descriptive analytical approach in order to clarify the causal relationship between variables, however it conducted an empirical study to test the correlations in real practice. Empirically, the paper explores and identifies the perceived levels of OJ, JS, and OCB among a small-sized sample of employees working at the Ministry of Transportation; a crucial Egyptian public organization, and then it examines the impact of OJ determinants on OCB practices there including the intervening influence of employees’ JS. Survey-based data was collected by using questionnaires of (104) respondents from the ministry. The research concluded that fairness perceptions, particularly those derived from OJ major determinants, are instrumental in predicting the occurrence of OCB in public sector organizations. Also, the results proved that OJ and JS contribute positively to OCB dimensions at the Ministry of Transportation. In fact, it makes a distinct enrichment to the field of study; is that it might be the first to investigate and analyze the effect of OJ on OCB through JS, and it shows that OJ and JS could emerge as more significant predictors of OCBs in the public sector. At a practical level, this article contributes to boost the applicability and meaningfulness of these concepts in the Egyptian culture. While OJ has an essential role in enhancing JS and OCB, results of this research can be beneficial in promoting OJ in public organizations, subsequently more OCBs, and finally improving organizational performance. So, the study provides profitable findings and helpful recommendations which can be applied by Egyptian public executives.